2014
DOI: 10.3892/or.2014.3377
|View full text |Cite
|
Sign up to set email alerts
|

AQP5: A novel biomarker that predicts poor clinical outcome in colorectal cancer

Abstract: Abstract. The aquaporins (AQPs) are water channel proteins that exhibit several properties related to tumor development. However, the expression and clinical significance of AQP5 in colorectal cancer, particularly the correlation with circulating tumor cells (CTCs), has not been elucidated. The aim of the present study was to determine whether or not the expression of AQP5 is a strong prognostic biomarker for colorectal cancer. The results showed that of 45 tumor specimens, 14 (31.1%) had high levels of expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…Increasing evidences had demonstrated that AQPs were involved in the progression of different cancers, such as colon cancer, lung cancer, gastric cancer, and breast cancer . In particular, AQP5 was found to be implicated in the incidence and progression of CRC, and closely related to CRC metastasis . However, there is no evidence to explain the effect of AQP5 on EMT of CRC to date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing evidences had demonstrated that AQPs were involved in the progression of different cancers, such as colon cancer, lung cancer, gastric cancer, and breast cancer . In particular, AQP5 was found to be implicated in the incidence and progression of CRC, and closely related to CRC metastasis . However, there is no evidence to explain the effect of AQP5 on EMT of CRC to date.…”
Section: Discussionmentioning
confidence: 99%
“…37,44,45 In particular, AQP5 was found to be implicated in the incidence and progression of CRC, and closely related to CRC metastasis. 23 However, there is no evidence to explain the effect of AQP5 on EMT of CRC to date. In this study, we observed that overexpression of AQP5 promoted the mesenchymallike phenotype and EMT process in SW480 and HCT-116 cells as well as the low metastatic HT-29 CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AQP5 as a critical member of AQP family was first cloned from rat submandibular gland [7], and has been shown to contribute to the progression of various types of malignant tumors [8][9][10][11][12]. Recent studies reveal AQP5 as an oncogene involved in carcinogenesis [13] and suggest it as a novel prognostic biomarker for various types of tumors [14,15]. Interestingly, an abnormal overexpression of AQP5 has been found in colorectal cancer samples, which is linked to the aggressiveness and metastasis [15,16].…”
mentioning
confidence: 99%